Controlling internal nitrogen and phosphorus loading using Ca-poor soil capping in shallow eutrophic lakes: Long-term effects and mechanisms. (15th April 2023) - Sun, Chuanzhe; Zhong, Jicheng; Pan, Gang; Mortimer, Robert J.G.; Yu, Juhua; Wen, Shuailong; Zhang, Lei; Yin, Hongbin; Fan, Chengxin
Highlights: Effect of clean soil capping on internal loading was studied via a field experiment. Ca-poor soil capping can effectively inhibit the release of N and P for one year. Ca-poor soil showed excellent P adsorption and retention capacity. Waterbody supply of Ca to the Ca-poor soil captured P in the porewater to form Ca-P. Abstract: Clean soil is a potential capping material for controlling internal nutrient loading and helping the recovery of macrophytes in eutrophic lakes, but the long-term effects and underlying mechanisms of clean soil capping under in-situ conditions remain poorly understood. In this study, a three-year field capping enclosure experiment combining intact sediment core incubation, in-situ porewater sampling, isotherm adsorption experiments and analysis of sediment nitrogen (N) and phosphorus (P) fractions was conducted to assess the long-term performance of clean soil capping on internal loading in Lake Taihu. Our results indicate that clean soil has excellent P adsorption and retention capacity as an ecologically safe capping material and can effectively mitigate NH4 + -N and SRP (soluble reactive P) fluxes at the sediment-water interface (SWI) and porewater SRP concentration for one year after capping. The mean NH4 + -N and SRP fluxes of capping sediment were 34.86 mg m −2 h −1 and -1.58 mg m −2 h −1, compared 82.99 mg m −2 h −1 and 6.29 mg m −2 h −1 for control sediment. Clean soil controls internal NH4 + -N release through cation (mainly Al 3+ ) exchange mechanisms, while for SRP, clean soil can not only react with SRP due to its high Al and Fe content, but also stimulate the migration of active Ca 2+ to the capping layer, thus precipitating as Ca-bound P (Ca-P). Clean soil capping also contributed to the restoration of macrophytes during the growing season. However, the effect of controlling internal nutrient loading only lasted for one year under in-situ conditions, after which the sediment properties returned to pre-capping conditions. Our results highlight that clean Ca-poor soil is a promising capping material and further research is needed to extend the longevity of this geoengineering technology. Graphical abstract: Image, graphical abstract